Longitudinal thalamic diffusion changes after middle cerebral artery infarcts. Issue 2 (14th January 2005) - Hervé, D; Molko, N; Pappata, S; Buffon, F; LeBihan, D; Bousser, M-G; Chabriat, H
Abstract : Background: Cerebral infarcts are responsible for functional alterations and microscopic tissue damage at distance from the ischaemic area. Such remote effects have been involved in stroke recovery. Thalamic hypometabolism is related to motor recovery in middle cerebral artery (MCA) infarcts but little is known concerning the tissue changes underlying these metabolic changes. Diffusion tensor imaging (DTI) is highly sensitive to microstructural tissue alterations and can be used to quantify in vivo the longitudinal microscopic tissue changes occurring in the thalamus after MCA infarcts in humans. Methods: Nine patients underwent DTI after an isolated MCA infarct. Mean diffusivity (MD), fractional anisotropy (FA), and thalamic region volume were measured from the first week to the sixth month after stroke onset in these patients and in 10 age matched controls. Results: MD significantly increased in the ipsilateral thalamus between the first and the sixth month (0.766×10 −3 mm 2 /s first month; 0.792×10 −3 mm 2 /s third month; 0.806×10 −3 mm 2 /s sixth month). No significant modification of FA was detected. In six patients, the ipsilateral/contralateral index of MD was higher than the upper limit of the 95% CI calculated in 10 age matched controls. An early decrease of MD preceded the increase of ipsilateral thalamic diffusion in one patient at the first week and in two other patients at the first month. Conclusion: After MCA infarcts, an increase in diffusion is observed with DTI in the ipsilateral thalamus later than 1 month after the stroke onset. This is presumably because of the progressive loss of neurons and/or glial cells. In some patients, this increase is preceded by a transient decrease in diffusion possibly related to an early swelling of these cells or to microglial activation. Further studies in larger series are needed to assess the clinical correlates of these findings.